FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PENGETAHUAN PEGAWAI MENGENAI KESELAMATAN PASIEN PADA PUSKESMAS RAWAT INAP KOTA DENPASAR - Widya Sari, Ni Nyoman Intan; Indrayathi, Putu Ayu (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 3 (2021): Desember 2021, 2022)
ABSTRACT Patient safety is a system that makes patient care safer. With the COVID-19 pandemic, healthcare facilities have challenges in ensuring and improving patient safety. This research aims to investigate the factors related to the level of knowledge of primary health care (Puskesmas) officers on the safety of patients at an Inpatient Health Center in Denpasar City. It used descriptive quantitative research design with a cross-sectional study draft. Samples from this study are all employees of medical and non-medical health centers working in inpatient health centers denpasar, namely 124 respondents, sampling techniques using the total sampling method. Univariate results using different tests of proportions showed the characteristics of employees in puskesmas there was no meaningful difference. Bivariate results using Simple Logistic Regression showed no relationship between age, gender, work experience, education level, training to knowledge level. Multivariate results using Binary Logistic Regression show that there is no significant difference (Ho is accepted). Provide training to puskesmas employees, evaluate the quality of services, develop performance standards, form patient safety teams and optimize their role and improve the recording, reporting and data storage systems. Keywords: Knowledge, Patient Safety, Primary Health Care , Officers, Inpatient Health Center